Single fetal demise in monochorionic pregnancies: incidence and patterns of cerebral injury. (1st February 2015) - van Klink, J. M. M.; van Steenis, A.; Steggerda, S. J.; Genova, L.; Sueters, M.; Oepkes, D.; Lopriore, E.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 247–247 ABSTRACT: Objective: To evaluate the incidence, type and severity of cerebral injury in the surviving monochorionic (MC) cotwin after single fetal demise in twin pregnancies. Methods: All MC pregnancies with single fetal demise that were evaluated at the Leiden University Medical Center between 2002 and 2013 were included. Perinatal characteristics, neonatal outcome and the presence of cerebral injury, observed on neuroimaging, were recorded for all cotwin survivors. Results: A total of 49 MC pregnancies with single fetal demise, including one MC triplet, were included in the study ( n = 50 cotwins). Median gestational age at occurrence of single fetal demise was 25 weeks and median interval between single fetal demise and live birth was 61 days, with a median gestational age at birth of 36 weeks. Severe cerebral injury was diagnosed in 13 (26%) of the 50 cotwins and was detected antenatally in 4/50 (8%) and postnatally in 9/50 (18%) cases. Cerebral injury was mostly due to hypoxic‐ischemic injury resulting in cystic periventricular leukomalacia, middle cerebral artery infarction or injury to basal ganglia, thalamus and/or cortex. Risk factors associated with severe cerebral injury were advanced gestational age at the occurrence of single fetal demise (odds ratio (OR), 1.14 (95% CI, 1.01–1.29) for each week of gestation; P = 0.03), twin–twin transfusion syndrome developing prior to single fetal demise (OR, 5.0 (95% CI, 1.30–19.13); P = 0.02) and a lower gestational age at birth (OR, 0.83 (95% CI, 0.69–0.99) for each week of gestation; P = 0.04). Conclusions: Single fetal demise in MC pregnancies is associated with severe cerebral injury occurring in 1 in 4 surviving cotwins. Routine antenatal and postnatal neuroimaging, followed by standardized long‐term follow‐up, is mandatory. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.